2013
DOI: 10.3324/haematol.2013.087114
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of interleukin-6 and hepcidin antimicrobial peptide in the development of anemia with age

Abstract: Anemia is common in older adults and associated with adverse health outcomes in epidemiological studies. A thorough understanding of the complex pathophysiological mechanisms driving anemia in the elderly is lacking; but inflammation, iron restriction, and impaired erythroid maturation are thought to influence the phenotype. We hypothesized that interleukin-6 contributes to this anemia, given its pro-inflammatory activities, its ability to induce hepcidin antimicrobial peptide, and its negative impact on sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
(61 reference statements)
4
17
0
2
Order By: Relevance
“…Samples were thawed once, then analyzed by the Clinical Research Unit of the Johns Hopkins Institute for Clinical and Translational Research for pro-inflammatory cytokines interferon gamma, IL-1 beta, IL-6, keratinocyte-derived cytokine, and tumor necrosis factor alpha, using multiplex analysis (Meso Scale Discovery, Gaithersburg, MD). This multiplex ELISA reported IL-6 values above background for the IL-6 (−/−) mice, as we have previously reported [25]. We conclude that the ELISA probe may bind to incomplete IL-6 proteins due to the insertion of a stop codon in the middle of the IL-6 gene.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Samples were thawed once, then analyzed by the Clinical Research Unit of the Johns Hopkins Institute for Clinical and Translational Research for pro-inflammatory cytokines interferon gamma, IL-1 beta, IL-6, keratinocyte-derived cytokine, and tumor necrosis factor alpha, using multiplex analysis (Meso Scale Discovery, Gaithersburg, MD). This multiplex ELISA reported IL-6 values above background for the IL-6 (−/−) mice, as we have previously reported [25]. We conclude that the ELISA probe may bind to incomplete IL-6 proteins due to the insertion of a stop codon in the middle of the IL-6 gene.…”
Section: Methodssupporting
confidence: 86%
“…No IL-6 (+/−) mice were used. The data for untreated IL-6 (−/−) mice, only, also appear in a separate publication developed in parallel with this one [25]. …”
Section: Methodsmentioning
confidence: 99%
“…In a mouse model of anemia of aging [3], older mice exhibited reduced hemoglobin, reduced erythrocyte numbers, increased myeloid lineage cells, and increased IL6 and IFNγ. Although hepcidin was not higher, it may have been inappropriately high relative to the degree of anemia.…”
Section: Hepcidin and The Pathogenesis Of Aimentioning
confidence: 99%
“…This disorder has been termed anemia of inflammation (AI) or anemia of chronic disease, and is the second most common form of anemia worldwide [1*-2]. A similar condition is seen in the elderly, although often in the absence of a specific underlying disease [3]. Typically, AI is normocytic, normochromic, and mild to moderately severe.…”
Section: Introductionmentioning
confidence: 99%
“…This anemia has been attributed to low grade inflammation; however, the cause of this inflammation is often not explained by infection, CKD, or cancer and has been termed the unexplained anemia of the elderly. Studies in aged mice demonstrate that IL-6 and hepcidin are not directly required for aging-related anemia; however, mice lacking these genes have improved erythropoiesis later in life (89). More recent work has demonstrated that patients with unexplained anemia of the elderly, all of whom have no known history of chronic inflammatory disease, do in fact have features of low grade inflammation including elevated IL-6 expression (90).…”
Section: Other Causes Of the Anemia Of Inflammationmentioning
confidence: 99%